Milking twice daily in the presence of a cow’s own calf fails to prolong postpartum anestrus - Lamb, G.C.; Lynch, J.M.; Miller, B.L.; Grieger, David M.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Six treatment s were initiated approximately 15 days after calving: 1) calf was weaned permanently from its dam (calf weaned; CW); 2) calf was present continuously with its dam but contact with the udder was prohibited (calf restricted; CR); 3) calf was present continuously with its dam (calf present; CP); 4) CR dam was suckled twice daily by her own calf (CR+S2×); 5) CW dam was milked twice daily (CW+M2×); 6) CR dam was milked twice daily (CR+ M2×). During the 4-week treatment period , cows in the CR+M2× treatment had twofold greater yield milk and milk components than CW+M2× cows. After completing treatments, calves were returned to their dams and allowed to suckle ad libitum. At the time when suckling was reestablished, milk yield was greatest in CP cows, followed by CR+S2×, CR+M2×, and CW+M2× cows, respectively. Although, lactation in CW an dCR cows ceased, it was reinitiated after 1 week of renewed suckling, and increased further by 5 weeks. Cows milked twice daily (CR+M2× and CW+M2×) h ad their first postpartum ovulation about 2 weeks after weaning, similar to cows not milked or suckled (CW and CR). In contrast, cows suckled by their calves either twice daily (CR+S2×) or ad libitum (CP) first ovulated about 5 weeks after initiation of treatments. We concluded that milk removal by suckling, but not mechanically by milking 2× daily, is essential to prolong postpartum anestrus. Furthermore, suckling limited to 2× daily prolonged postpartum anestrus as much as ad libitum suckling.
Keywords: Beef; Milking; Suckling; Calf presence; Anestrus